(untitled) (World Bulletin of Social Sciences, 2026)
The article examines the transformation of methodological strategies for teaching the Russian language as a native, non-native, and foreign language in the context of inclusive education. It analyzes modern pedagogical approaches aimed at ensuring equal access to language education for learners with diverse educational needs. Particular attention is paid to the adaptation of teaching materials, the use of differentiated instruction, and the implementation of digital educational technologies.